Analysis of The Potential of Creative Economy Based on Local Wisdom in Soaib Village Kemtuk District, Jayapura Regency - Lazarus Ramandei; Sudiro Sudiro (Mandalika Institute, 2025)
This research aims to analyze the potential of local wisdom-based creative economy in Soaib Village, Kemtuk District, Jayapura Regency. Soaib Village has cultural wealth and abundant natural resources, including organic cocoa and orchids, which have the potential to be developed into a sustainable creative economy sector. The research method used a descriptive qualitative approach with data collection through observation, interviews, and documentation. Data analysis was conducted using the SWOT method, explanatory analysis, and Geographic Information System (GIS) to map the potential of existing resources. The results showed that organic cocoa and orchids are leading sectors that can drive the local economy. However, there are significant challenges such as limited infrastructure, lack of technical training, pest attacks on cocoa, and limited market access. Support from institutions such as WWF in providing training and mentoring has had a positive impact, especially in improving community skills related to forest product management and orchid cultivation. The implications of this research emphasize the importance of local wisdom as a foundation in creative economic development, while maintaining environmental sustainability. The resulting strategic recommendations include improving infrastructure, strengthening technical training, strengthening local institutions, and promoting awareness about the importance of sustainability.